Randomized clinical trial quantifying the effectiveness of a self-monitoring intervention in cancer patients with peripheral neuropathy: A quantitative study - Kiyoko Kanda; Kazuko Ishida; Ayumi Kyota; Chiaki Ishihara; Keiko Fujimoto; Mai Hosokawa; Ruka Mochizuki (Elsevier, 2023)
Objective: The aim of this study was to quantitatively evaluate the efficacy of a self-monitoring intervention for the management of persistent chemotherapy-induced peripheral neuropathy (CIPN). Methods: A randomized controlled clinical trial was conducted on 65 outpatients receiving taxane or platinum-based anticancer drugs. Participants were assigned to the control group (CG; n ​= ​32) or the self-monitoring group (SMG; n ​= ​33) and followed for 6 weeks. Non-interveners were blinded. Participants in the intervention group self-monitored and recorded. The researchers provided feedback on the recorded symptoms and coping strategies once every 3 weeks. The efficacy of the 6-week self-monitoring intervention was assessed, using various measures, at baseline (T0), 3 weeks (T1), and 6 weeks (T2). Scores of CIPN, Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity, Distress and Impact Thermometer, Self-Efficacy Scale for Advanced Cancer, and Functional Assessment of Cancer Therapy-General of both groups were compared. Safety behavior in daily life was also compared. The study was conducted from August 9, 2017 to March 30, 2020 in outpatient clinics at three hospitals. Analysis was conducted using the t-test, Mann-Whitney U test, χ2 test, and two-way repeated-measures analysis of variance (two-way RMANOVA). Results: No significant differences were noted between the two groups in the CIPN score, the Distress and Impact Thermometer score, and in safety behavior in daily life. The mean Self-Efficacy Scale for Advanced Cancer score at T1 differed between the two groups (CG mean ​± ​SD: 358.44 ​± ​109.90; SMG mean ​± ​SD: 421.21 ​± ​85.54), which was significantly higher in the SMG (P ​= ​0.012). Two-way RMANOVA revealed an interaction between the CG and SMG (F ​= ​5.689, P ​= ​0.004). Quality of life scores were higher in the SMG than in the CG at T0, T1, and T2. Two-way RMANOVA analysis showed an effect of the intervention (F ​= ​7.914, P ​= ​0.007). Conclusions: The self-monitoring intervention maintained the participants' quality of life. This finding suggests its effectiveness in patients with peripheral neuropathy.